Registration of 'Warhorse' Wheat. Issue 2 (2nd May 2014) - Berg, J. E.; Lamb, P. F.; Miller, J. H.; Wichman, D. M.; Stougaard, R. N.; Eckhoff, J. L.; Kephart, K. D.; Nash, D. L.; Grey, W. E.; Gettel, D.; Larson, R.; Jin, Y.; et al.
Abstract : 'Warhorse' (Reg. No. CV‐1096, PI 670157) hard red winter (HRW) wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in September 2013. Warhorse is of unknown pedigree, derived from a composite of three topcrosses made to the same F1 population in 2000: MT9908//'Nuplains'/MTS9862; Nuplains/MTS9862//MTW0047; and Nuplains/MTS9862//MTS0028. Warhorse was developed using a modified bulk breeding method and selected as an F5:6 headrow. Warhorse was tested under the experimental number MTS0808 from 2008 to 2013 in Montana. Quality was evaluated in multilocation Montana trials since 2008. Warhorse is a solid‐stem, high‐yielding HRW wheat line with medium to high test weight, medium maturity, reduced height ( Rht‐B1b ), medium to high grain protein, and acceptable milling and baking quality. Warhorse was released for its improved host plant resistance to wheat stem sawfly ( Cephus cinctus Nort.) conditioned by stem solidness, along with short stature and improved yield potential relative to existing solid‐stem cultivars adapted to Montana.